Total rectosigmoidectomy versus partial rectal resection in primary debulking surgery for advanced ovarian cancer. Issue 3 (March 2016) - Plotti, F.; Montera, R.; Aloisi, A.; Scaletta, G.; Capriglione, S.; Luvero, D.; De Cicco Nardone, C.; Basile, S.; Benedetti Panici, P.; Angioli, R.
Abstract: Purpose: To compare in a sample of Italian patients intraoperative, perioperative complications, Quality of Life (QoL), recurrence rate and overall survival of advanced ovarian cancer (AOC) patients according to the type of surgery performed on sigma-rectum, total rectosigmoid resection (TRR) versus partial rectosigmoid resection (PRR). Methods: From May 2004 to May 2010, consecutive patients affected by epithelial AOC (FIGO Stage III–IV) were assessed for this prospective case–control study, According to the type of colorectal surgery performed to approach rectosigmoid involvement, patients were allocated into Group A (TRR) and Group B (PRR). PRR was performed when the complete removal of disease led to a laceration <30–40% of intestinal wall circumference. Results: 82 and 72 patients were included in Group A and Group B respectively. Surgical outcomes were statistically similar except hospital stay which was significantly lower in the PRR group. There was not a statistically significant difference as regarding intra-operative, perioperative and postoperative complications, even if a higher rate of major complications were recorded in TRR. An improvement in QoL's scores has been recorded in PRR's group. There was not a statistically difference concerning the optimal debulking rate (92% and 96% respectively) and 5-year Overall Survival (48% and 52% respectively). Conclusions: PRR seems to be feasible in over 40% of patients with advanced ovarian cancer and recto-sigmoid colon involvement. It is related to higher QoL and can be easily performed, without jeopardizing surgical radicality, in those cases in which conservative surgery at intestinal tract does not compromise residual tumor.